Will the US5 million onasemnogene abeparvosec treatment for spinal muscular atrophy represent 'value for money' for the NHS? A rapid inquiry into suggestions that it may be cost-effective. (2nd July 2020) - Connock, Martin; Andronis, Lazaros; Auguste, Peter; Dussart, Claude; Armoiry, Xavier
ABSTRACT: Objectives: Nusinersen (Spinraza®, Biogen) and onasemnogene abeparvosec (Zolgensma®, Novartis) are novel gene-based therapies for the orphan disease Spinal Muscular Atrophy. Onasemnogene abeparvosec has been allocated an acquisition cost of up to US5 million per patient. We undertook a rapid inquiry to evaluate if onasemnogene abeparvosec is likely to be cost-effective for the UK NHS. Methods: We used publicly available cost-effectiveness data and recommended methodology to perform cost-utility evaluation of onasemnogene abeparvosec versus best supportive care and nusinersen. Results: Our evaluations highlight wide variations in cost and benefit estimates of nusinersen and indicate that onasemnogene abeparvosec is unlikely to represent value for money according to current standards of reimbursement. Results are discussed in the context of reimbursement decisions for orphan diseases. Conclusion: Commonly implemented commercial confidentiality practices combined with uncertain data obscure scrutiny and justification of past and present reimbursement decisions for orphan drugs. Future cutting edge expensive therapies will be numerous, they will entail very substantial economic strains. We conclude that there is an urgent and increasing need for the development of improved procedures that can lead to equitable, consistent, and transparent decision-making.